Indian Start-ups Lure Silicoln Valley Cash. - Perry, T.S.
Having discovered India's inexpensive engineering talent years ago, nearly every big tech company has a subsidiary there. Now the venture capital (VC) groups of these multinationals are discovering India's independent start-ups. Venture capital investment in India is on the way to a substantial increase this year, with US 341 million dollars committed in the first half of 2007. That follows VC's nearly doubling in 2006 to 508 million dollars spread over 90 deals. Nearly 15 percent of the 2006 money came from the venture capital divisions of companies like Cisco Systems, Google, IBM, Intel, and Yahoo, according to Arun Natarajan, CEO of Venture Intelligence, a Chennai-based firm that tracks VC investments. That's a much higher proportion than in the United States, where in 2006 big companies accounted for less than 8 percent of VC financing.
Keywords: Cisco Systems; Google; IBM; Indian start-ups.; Intel; Silicon Valley; VC financing; Yahoo; Centure capital investment; Independent start-ups.; Venture capital divisions